An indirect immunoperoxidase test for diagnosing Newcastle disease in chickens - I. P. R., Awang (1989)
An indirect immunoperoxidase test has been developed for the isolation and serological studies on the experimental infection of chickens with turkey paramyxovirus-3. The test is being used for diagnosing Newcastle disease in chickens.